THE INFLUENCE OF SOCIAL MEDIA ON TEACHING AND RESEARCH IN NIGERIAN HIGHER INSTITUITIONS. - AKINOLA, OLADIPUPO ABDULLAHI; OYEBIMPE, OYELEKAN CHARLOTTE; ADEWOLE, ADEDEJI BABATUNDE (JOURNAL OF ADVANCES IN LINGUISTICS, 2016)
Social media is a communication tool that was originally designed as a way for friends, family, or other groups of people to engage in discussions and interactions. They allow members to explore new opportunities and experiences. However, social media sites have now become an invaluable tool for teaching, learning and research at all levels of education most especially, in higher institutions. This paper therefore identifies different types of social media that are predominant in Nigeria and also examine different ways of using them to enhance teaching and research in Nigerian higher institutions.